2007
DOI: 10.1016/j.jcp.2007.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Poloidal–toroidal decomposition in a finite cylinder. I: Influence matrices for the magnetohydrodynamic equations

Abstract: The Navier-Stokes equations and magnetohydrodynamics equations are written in terms of poloidal and toroidal potentials in a finite cylinder. This formulation insures that the velocity and magnetic fields are divergence-free by construction, but leads to systems of partial differential equations of higher order, whose boundary conditions are coupled. The influence matrix technique is used to transform these systems into decoupled parabolic and elliptic problems. The magnetic field in the induction equation is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 32 publications
(61 reference statements)
1
24
0
Order By: Relevance
“…Thus, there is a gauge freedom for the boundary conditions. The most simple and commonly used gauge condition for ξ is ξ| r=R = 0 (3.8) (Marques et al 1993;Boronski & Tuckerman 2007). This gauge in combination with (3.2) and the no-slip condition on the velocity, u r | r=R = 0, yields…”
Section: Decomposition Of the Velocity Fieldmentioning
confidence: 99%
“…Thus, there is a gauge freedom for the boundary conditions. The most simple and commonly used gauge condition for ξ is ξ| r=R = 0 (3.8) (Marques et al 1993;Boronski & Tuckerman 2007). This gauge in combination with (3.2) and the no-slip condition on the velocity, u r | r=R = 0, yields…”
Section: Decomposition Of the Velocity Fieldmentioning
confidence: 99%
“…Several authors have applied Zernike polynomials to partial differential equations [101,102,72,86,15,16]. The Poisson equation is special because substituting the expansions…”
Section: Solving the Poisson Equation With Zernike Polynomialsmentioning
confidence: 99%
“…We now describe the ways in which we have validated the hydrodynamic code described here and in our companion paper [20]. We have obtained exact polynomial solutions to the nested Helmholtz-Poisson solver, which is by far the most complicated portion of the code; we present its form in the hopes it may prove useful to other researchers.…”
Section: Tests and Validationmentioning
confidence: 99%
“…Our main purpose here is to develop a mathematical and algorithmic tool which can be applied to von Kármán flow and to rotating turbulence, and which can be extended to the magnetohydrodynamic configuration of the VKS experiment [17]. In a companion article [20], we showed that this system could be reduced to the solution of a set of nested Helmholtz and Poisson problems with uncoupled Dirichlet boundary conditions, whose solutions could be superposed via the influence matrix technique. When applied to the Navier-Stokes equation in a finite cylinder, the resulting system has boundary conditions which are coupled and of high order.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation